Role Women's Digital Entrepreneurship Ecosystem in Emerging Economies - Abdul Ghonisyah, Ghaling Achmad; Asyiah, Ai Kusmiati (JMK (Jurnal Manajemen dan Kewirausahaan), 2025)
This study aims to analyze the digital entrepreneurship ecosystem of women and its role in emerging economies. With the advancement of digital technology, digital entrepreneurship has become a significant driver of economic growth, particularly among women. This research explores various factors influencing the digital entrepreneurship ecosystem, including access to technology, education, funding, networks, and existing regulations. The study adopts a qualitative approach, utilizing in-depth interviews and document analysis to understand the dynamics of women entrepreneurs in the digital sector. The findings reveal that, while digital entrepreneurship offers significant opportunities for women digital entrepreneurs, several challenges persist, such as limited access to resources, insufficient digital literacy, and gender inequality in business environments. By understanding this ecosystem, the research provides policy recommendations to support the development of women's digital entrepreneurship as a strategy for improving economic welfare and promoting social inclusion in Indonesia. In conclusion, the women's digital entrepreneurship ecosystem holds great potential to contribute to local economic development, but targeted policy interventions are necessary.